BISCAYAN TEACHERS AT FRANCOIST MILITARY COURTS (1937-1943) - Artetxe Sanchez, Karmele; Zubiaga Arana , Erik (Historia y Memoria de la Educación, 2024)
The present text analyzes the impact of the repression of the military jurisdiction on the Biscayan teaching profession during the immediate postwar period. The research deals with a historiographically unexplored issue, such as the integral study of the files opened against the teachers of the educational network of Bizkaia, taking into account both the sentences and the political profile of the defendants. Likewise, the most relevant characteristics of the different centers corresponding to the wide Biscayan school network are studied, as well as the establishment and operation of the main repressive machinery implemented after the victory of the rebels, such as the prosecutions processed by the military jurisdiction. The research includes a total of 588 cases (381 female teachers and 207 male teachers). Practically 7 out of 10 cases ended in dismissal, although this did not prevent the imposition of accessory sanctions. The most severely punished political profile corresponded to leftist and republican militants and sympathizers, followed by Basque nationalists. According to the results, we conclude that the military jurisdiction was not primarily aimed at the repression of the teaching profession, but that its objective was more general, the punishment of those considered hostile or dangerous to the new regime, especially if they had held positions of relevance or had played a significant role on the war front.